Earthworms from Matsu, Taiwan with descriptions of new species of the genera Amynthas (Oligochaeta: Megascolecidae) and Drawida (Oligochaeta: Moniligastridae) - Shen, Huei-Ping; Chang, Chih-Han; Chih, Wen-Jay (Zootaxa, 2015)
In 2012, we conducted earthworm surveys in Matsu Islands, and described five new species of the genera Amynthas and Metaphire and reported two new records, Desmogaster sinensis Gates, 1930 and Ocnerodrilus occidentalis Eisen, 1878. This paper describes three new species, one of them with two new subspecies, Amynthas nanganensis nanganensis sp. nov. et ssp. nov. and Amynthas nanganensis beiganensis ssp. nov., Drawida beiganica sp. nov. and Drawida dongyinica sp. nov., provides a new record of Drawida koreana Kobayashi, 1938 from the remaining specimens collected in the surveys, reports DNA barcodes (the 5’ end sequences of the mitochondrial cytochrome c oxidase subunit 1 gene) from type specimens and further reference specimens of the new species, and lists a total of 27 earthworm species and subspecies found from Matsu Islands. Pheretimoid earthworms made up 66.7% of the total number of the species, with Metaphire matsuensis Shen, 2014 and Metaphire californica (Kinberg, 1867) the most dominant. Our findings indicate that the earthworm fauna of Matsu Islands is more closely related to that of warm temperate China than to Taiwan or tropical southern China.